Evolving Concepts in how Viruses Impact Asthma - Altman, Matthew C. (J Allergy Clin Immunol, 2020)
Over the last decade, there have been substantial advances in our understanding about how viral infections regulate asthma (Table 1). Important lessons have been learned from birth cohort studies examining viral infections and subsequent asthma, understanding the relationships between host genetics and viral infections, the contributions of respiratory viral infections to patterns of immune development, the impact of environmental exposure on severity of viral infections, and how the viral genome influences host immune responses to viral infections. Further, there has been major progress in our knowledge about how bacteria regulate host immune responses in asthma pathogenesis. In this article, we also examine the dynamics of respiratory tract bacterial colonization during viral upper respiratory tract infection, in addition to the relationship of the gut and respiratory microbiomes with respiratory viral infections. Finally, we focus on potential interventions that could decrease virus-induced wheezing and asthma. There are emerging therapeutic options to decrease severity of wheezing exacerbations caused by respiratory viral infections. Primary prevention is a major goal and a strategy toward this end is considered.